Zur frage von den Theorie der Invarianten Affinen Zusammenhänge in der Li Gruppe - Vosylius, R. (Lithuanian Mathematical Journal, 1967)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:Р. В. Восилюс. К теории инвариантных аффинных связностей на группе ЛиR. Vosylius. Invariantinių afininių sąryšių Li grupėje teorijos klausimu